1992
DOI: 10.1247/csf.17.161
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Bacterial Lipopolysaccharide and Interferon-.GAMMA. on Proliferation of Two Factor-Dependent Macrophage Cell Lines.

Abstract: ABSTRACT. We examined the responsiveness of two factor-dependent macrophage cell lines, BDM-1and its subclone, BDM-1W3,to bacterial lipopolysaccharide (LPS), interferon-^(IFN-p), and tumor necrosis factor-a (TNF-a) for their growth. LPS inhibited the M-CSF-dependent proliferation of BDM-1 cells but it had no effect on the proliferation of BDM-1W3 cells. LPS promoted DNAsynthesis and supported the cell viability in the absence of CSFs in BDM-1and BDM-1W3 cells, suggesting that the intracellular signals are tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…LPS is mitogenic for some macrophage-like cell lines (Ohki et al, 1992) and has been shown to increase the survival of human monocytes in culture (Mangan et al, 1991;Becker et al, 1987) by preventing apoptosis. Alternatively, lipopolysaccharide could be acting by stimulating the small percentage of mature macrophages in cultures to release factors that enhance the proliferation of the less di#erentiated round cells (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is mitogenic for some macrophage-like cell lines (Ohki et al, 1992) and has been shown to increase the survival of human monocytes in culture (Mangan et al, 1991;Becker et al, 1987) by preventing apoptosis. Alternatively, lipopolysaccharide could be acting by stimulating the small percentage of mature macrophages in cultures to release factors that enhance the proliferation of the less di#erentiated round cells (see Fig.…”
Section: Discussionmentioning
confidence: 99%